TRANSFORMATION OF OCEANIC CRUST INTO CONTINENTAL CRUST IN THE PALEOSUBDUCTION ZONES OF THE TIEN SHAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The metamorphic complexes of the Tien Shan are composed mainly of metapelites and metabasites (eclogites, garnet amphibolites, amphibolites), which experienced metamorphism under high and ultrahigh pressures conditions, downgoing along the subduction zone to depths of 80–130 km.In these complexes, the primary basaltic oceanic crust (metabasites) and partly continental crust rocks (metapelites) were transformed into upper mantle rocks during subduction and, during exhumation, turned back into rocks with a density corresponding to the density of the continental crust. As a result, in the subduction channel the material of the oceanic crust was transformed into the continental crust.
Keywords: Tien-Shan, subduction, continental crust, oceanic crust, density of rocks.